The Transatlantic Trade and Investment Partnership: A critical perspective - Rainer Geiger (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2014)
The Transatlantic Trade and Investment Partnership offers great opportunity. This Perspective discusses the conditions for successfully concluding the agreement while avoiding the pitfalls of past investment treaty negotiations.
Keywords: 330